Analysis of stunting and malnutrition factors and implementation of community-based total sanitation - Aliyah, Nurul (Community Service for Sustainable Community Journal, 2024)
Background: Stunting and malnutrition remain important public health issues in rural areas. The prevalence of these conditions is closely linked to inadequate nutrition, poor sanitation, and suboptimal health practices. This study aimed to determine the prevalence of stunting and malnutrition among children, analyse contributing factors, and assess the effectiveness of community-based sanitation initiatives. Methods: A cross-sectional study was conducted involving 58 mothers of children under five. Data were collected using door-to-door questionnaires and anthropometric measurements focusing on height-for-age (TB/U) to assess the prevalence of stunting. Additional data were collected on infant feeding practices, sanitation behaviours, and immunisation coverage. Descriptive statistics were used to analyse findings, and STBM (Community-Based Total Sanitation) implementation was evaluated through community engagement and observation. Findings: Of the 60 children assessed, 39 (65%) were at risk of stunting. Anthropometric results showed that 16.7% of children had very short stature, while 18.3% were categorised as short. The prevalence of infectious diseases among children was 23.3%, and 8.3% had a history of low birth weight. Among adolescent girls, 75% had received TT immunisation, and all had normal nutritional status based on upper arm circumference (LILA) measurements. However, implementation of STBM practices was found to be lacking, with most communities not adopting good hygiene and sanitation behaviours. Conclusion: This study highlighted stunting and malnutrition as major health issues, with most children at risk. Poor sanitation and hygiene practices exacerbate these problems, underscoring the need for comprehensive health education and improved sanitation infrastructure. Interventions focusing on maternal education, nutrition, and community-based sanitation programmes are essential to address these issues. Novelty/Originality of this article: This study provides valuable insights into the linkages between stunting, malnutrition and community sanitation practices in rural areas of Indonesia. It is one of the first studies to evaluate the role of STBM in addressing these health challenges, providing a foundation for targeted interventions to improve community health outcomes.